2009
DOI: 10.1007/s00167-008-0701-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting anterior cruciate ligament integrity in patients with osteoarthritis

Abstract: This study looks at the difference between the macroscopic and microscopic appearances of the anterior cruciate ligament (ACL) in a sample of 55 consecutive patients admitted for routine total knee replacement for osteoarthritis. At the time of surgery the macroscopic appearance of the ACL was classified as normal, moderately damaged (fissured) or completely ruptured. The excised ACL was sent for histological examination and grading. The macroscopic appearance of the ACL at surgery was compared to the severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
(26 reference statements)
1
11
0
1
Order By: Relevance
“…Thus, knowledge of ACL integrity prior to use of these implants is paramount, as partial ruptures and fissuring have been shown to significantly affect the histological and functional characteristics of the ACL. 27 An accurate assessment of the integrity of the ACL prior to operating will help to guide the surgeon to the possible options of joint replacement in each case, as well as manage the patients' expectations and the consent process. As we replace the knee in the younger and younger individual, we are striving to maintain, as close to normal, the biomechanics and function of the knee joint, for which an intact and functioning ACL is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, knowledge of ACL integrity prior to use of these implants is paramount, as partial ruptures and fissuring have been shown to significantly affect the histological and functional characteristics of the ACL. 27 An accurate assessment of the integrity of the ACL prior to operating will help to guide the surgeon to the possible options of joint replacement in each case, as well as manage the patients' expectations and the consent process. As we replace the knee in the younger and younger individual, we are striving to maintain, as close to normal, the biomechanics and function of the knee joint, for which an intact and functioning ACL is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanisms of CCL pathology are undefined, predisposed dogs have thinner collagen fibrils in weaker CCLs that have increased expression of matrix metalloproteinase 2 than those of cruciate disease-resistant breeds such as Greyhounds 82 . Importantly, although ACL rupture in young humans is generally considered to be traumatic in cause, ~70% of macroscopically normal human ACLs also have histological evidence of pathology consistent with early degeneration 89 . Genetics.…”
Section: Knee Cruciate Ligament Rupturementioning
confidence: 99%
“…This could be partly explained by work by Trompeter et al who showed that patients with macroscopically normal ACLs in arthritic knees actually showed significant signs of histological degeneration. 36 Citak et al demonstrated that with respect to the Lachman and the pivot shift tests, single-bundle ACL reconstruction restored kinematics in the UKA knee to magnitudes similar to those in the ACL-intact knee. 37 An in vivo kinematic study by Pandit et al demonstrated that normal knee kinematics is achieved in the ACL-deficient arthritic knee, following ACL reconstruction and UKA.…”
Section: Is Anterior Cruciate Ligament Deficiency a Contraindication mentioning
confidence: 99%